STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA HINDU DALAM MENUMBUHKEMBANGKAN KEMAMPUAN LITERASI DI SMP PETRA BERKAT - Ayu Indah Cahyani; I Ketut Sudarsana (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2022)
The purpose of this study was to describe learning strategies for Hindu religious education in developing literacy skills at Petra Berkat Junior High School. This type of research is qualitative with data collection methods using observations, interviews and literature studies. The results of the study show that the lack of interest in reading books (literacy) and critical thinking skills among students is one of the obstacles that occur in the world of education in Indonesia today. This is based on the fact that some students who lack interest in reading have not been able to think critically in processing and obtaining reliable and actionable information. Therefore, efforts are needed or strategies and methods used in learning to grow students' reading abilities and interests so that students can have critical thinking skills in processing the information obtained in the hope of creating a golden generation that is able to compete in today's era.Keywords: Literacy Ability; Learning strategies; Hindu Religious Education